Living Beyond Means as Reflected in Old Russian Proverbs - Vernikov, Andrei; Kurysheva, Anna (Journal of Economic Sociology, 2023)
This paper has its focus on the popular discourse of Russian people regarding living on credit and consumer debt. Proverbs and sayings serve as empirical material containing the institutions that shape economic culture of a certain historical period. We studied the relevant sections of the collection “Proverbs of the Russian People” published by Vladimir Ivanovich Dahl in 1862. The identified elements of discourse are combined into three groups: (1) living within one’s means and what impedes it; (2) borrowing by households; and (3) private lending. The main empirical result is that popular discourse, which prevailed until mid-19th century at least, was blatantly critical of debt bond and the phenomena that led to it by undermining the financial viability of a household. These are, primarily, overconsumption, consumerism, and excessive impulsive spending. Some of the value commandments encourage financial prudence and self-reliance based on self-restraint in consumption and spending. Other value commandments attack the properties which erode the foundation for self-reliance and financial prudence. The principles of self-restraint and self-reliance resonate with the contemporary ideas of sustainable development. We argue that further research in the direction that we earmark might change the sign of the existing judgments regarding Russian traditional economic culture, which seems to be a topical and relevant matter nowadays.